2014
DOI: 10.5935/abc.20140109
|View full text |Cite
|
Sign up to set email alerts
|

Ivabradine Improves Heart Rate Variability in Patients with Nonischemic Dilated Cardiomyopathy

Abstract: BackgroundIvabradine is a novel specific heart rate (HR)-lowering agent that improves event-free survival in patients with heart failure (HF).ObjectivesWe aimed to evaluate the effect of ivabradine on time domain indices of heart rate variability (HRV) in patients with HF.MethodsForty-eight patients with compensated HF of nonischemic origin were included. Ivabradine treatment was initiated according to the latest HF guidelines. For HRV analysis, 24-h Holter recording was obtained from each patient before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
5
28
0
1
Order By: Relevance
“…Clinical studies have documented that the administration of Ivabradine to patients suffering from nonischemic heart failure enhances time domain measures of HRV [15]. At the same time, an in vitro study, using human ESC-derived cardiomyocytes, concluded that 10 -6 M Ivabradine does not affect BRV [6].…”
Section: Ivabradinementioning
confidence: 98%
See 1 more Smart Citation
“…Clinical studies have documented that the administration of Ivabradine to patients suffering from nonischemic heart failure enhances time domain measures of HRV [15]. At the same time, an in vitro study, using human ESC-derived cardiomyocytes, concluded that 10 -6 M Ivabradine does not affect BRV [6].…”
Section: Ivabradinementioning
confidence: 98%
“…Several studies investigated the effects of antiarrhythmic drugs on HRV in diseased as well as healthy individuals. Ivabradine, Verapamil and Sotalol, for instance, have been reported to increase HRV parameters in patient groups suffering from various cardiac diseases [14][15][16]. In contrast, Flecainide has been found to decrease HRV parameters in patients after acute myocardial infarction as well as in patients without structural heart disease [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although Atenolol has been used in some cases, Metoprolol or Carvedilol remains a more rational choice of beta blocker in this case scenario. 14 Ivabradine was also found to be used in 1.54% cases in our study. This use is supported in recent literature due to its heart rate lowering effect.…”
Section: Discussionmentioning
confidence: 77%
“…This use is supported in recent literature due to its heart rate lowering effect. [14][15][16] Ivabradine has a beneficial effect in DCM especially in those who have heart rates not controlled with beta blockers. In few patients due to the heart rate lowering effect of beta blockers, syncope occurred and in those cases Digoxin was used as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Possible improvement in patient quality of life has also been noted. [6][7][8][9][10][11] Ivabradine may also decrease aortic stiffness after 1 year of treatment. 8 A few studies have also evaluated the potential role of ivabradine in the treatment of sinus tachycardia, postural orthostatic tachycardia syndrome, vasovagal syncope, and multiple organ dysfunction.…”
Section: Indicationsmentioning
confidence: 99%